COALMOD-world: A model to assess international coal markets until 2030 - Clemens Haftendorn; Franziska Holz; Christian von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Coal continues to be an important fuel in many countries' energy mix and, despite the climate change concerns, it is likely to maintain this position for the next decades. In this paper a numerical model is developed to investigate the evolution of the international market for steam coal, the coal type used for electricity generation. The main focus is on future trade ows and investments in production and transport infrastructure until 2030. COALMOD-World is an equilibrium model, formulated in the complementarity format. It includes all major steam coal exporting and importing countries and represents the international trade as one globalized market. Some suppliers of coal are at the same time major consumers, such as the USA and China. Therefore, domestic markets are also included in the model to analyze their interaction with the international market. Because of the different qualities of steam coal, we include different heating values depending on the origin of the coal. At the same time we observe the mass-specific constraints on production, transport and export capacity. The time horizon of our analysis is until 2030, in 5-year steps. Production costs change endogenously over time. Moreover, endogenous investments are included based on a net present value optimization approach and and the shadow prices of capacities constraints. Investments can be carried out in production, inland freight capacities (rail in most countries), and export terminals. The paper finishes with an application of the model to a base case scenario and suggestions for alternative scenarios.
Keywords: L11; L72; C69; 330; Coal; energy; numerical modeling; investments; international trade; Kohlenmarkt; Prognose; Kohle; Außenhandel; Wirtschaftsmodell; Szenariotechnik; Welt